Effect of Arc Welding Amperage on the Toughness of Low Alloy Steel - Kesuma, Andri Arif; , Rinaldi; , Sepfitrah; J, Abdul Khair (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
This paper is to study the effect of arc welding amperage variation on the mechanical properties by using shielded metal arc welding (SMAW) E 6013 to the joint of metal that comply with ASTM E23. In the welding joint zone is always to be concern due to fusion and heating treatment that cause the change of material properties after welding process. In order to ensure the toughness of weld joint material, so tensile and charpy test are conducted to observe the properties of weld joint material. The charpy V-notch impact indicate the increasing of heat input lead to be more brittle in the weld zone.